Novel oil extraction methods in food industry: A review - Bazilla Gayas,; Gagandeep Kaur, (Journal of Oilseed Brassica, 2026)
Many fruits and cereals contain essential oils which are attaining importance in food, drug, and cosmeticindustries owing to their desirability, and nutraceutical properties. Soxhlet extraction is the method used forisolation of oil from plant material. Usually, plant materials are subjected to mechanical shear using expellersto release the volatiles in virgin state. A new method of extraction has been solvent extraction involving useof polar solvents. The disadvantage with the process is the use of hazardous, and flammable liquid organicsolvents, potentially toxic emission during extraction, non-selective extraction, and time consuming. In orderto obtain a good yield from extraction as well as to prevent the uses of volatiles, correct alternative of solventis very important. Novel extraction methods like ultra sound extraction, microwave assisted extraction, andsupercritical fluid extraction has been successfully employed for extraction of oils with higher yield, andbetter physiochemical, and functional properties. This article reviews the recent work on extraction usingnovel methods like ultra sound extraction, microwave assisted extraction, and supercritical fluid extraction.